Shadows on the sea - Harlow, Joan Hiatt (New York : Aladdin Paperbacks, 2005)
In 1942, fourteen-year-old Jill goes to stay with her grandmother on the coast of Maine, where she is introduced to the often gossipy nature of small-town life, and discovers that the war is closer than she thought.
6.6
5-8
5-8.
Publisher's Weekly
Booklist
Bulletin (Center for Children's books)
Keywords: World War, 1939-1945 -- Maine -- Juvenile fiction; World War, 1939-1945 -- United States -- Fiction; Grandmothers -- Fiction; Friendship -- Fiction; Maine -- Fiction; Historical fiction; World War, 1939-1945 -- United States -- Fiction; Grandmothers -- Fiction; Friendship -- Fiction; Maine -- Fiction; Historical fiction